2015
DOI: 10.1007/978-3-319-22671-2_11
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in Essential Hypertension and Blood Pressure Regulation

Abstract: Unravelling the complete genetic predisposition to high blood pressure (BP) has proven to be challenging. This puzzle and the fact that coding regions of the genome account for less than 2 % of the entire human DNA support the hypothesis that mechanisms besides coding genes are likely to contribute to BP regulation. Non-coding RNAs, especially microRNAs, are emerging as key players of transcription regulation in both health and disease states. They control basic functions in virtually all cell types relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…The importance of microRNAs in cardiovascular diseases is rising (Marques and Charchar, 2015). In vivo studies showed that angiotensin II induced changes in the microRNA profile during hypertension (Eskildsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of microRNAs in cardiovascular diseases is rising (Marques and Charchar, 2015). In vivo studies showed that angiotensin II induced changes in the microRNA profile during hypertension (Eskildsen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs in the regulation of cardiovascular diseases has attracted broad research interest (Marques and Charchar, 2015;Kontaraki et al, 2014). Racial differences of miRNA expression have also been demonstrated in the case of hypertension (Dluzen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic profiles that characterise hypertension in rodent models have been established [24] and first data in human kidneys point towards differences in the expression of the gene encoding renin between hypertensive and normotensive individuals [25]. Studies into the regulation of gene expression and in particular into microRNAs are of interest in this context [26]. A recent example shows that circulating levels of miR-181a are a surrogate for renal miR-181a expression where it colocalises with renin particularly in collecting ducts and that this microRNA is differentially regulated between hypertensive and normotensive subjects [27].…”
Section: Genetic Aspects and "Omics"mentioning
confidence: 99%